The Blue Tent: a pilot experience of the Order of Malta’s Italian Relief Corps (CISOM) to face the family need of caring for young children during public events. - Parmigiani, Stefano; Mazzei, Ilaria; Lalli, Emilio; Vaudano Lalli, Elena; Pasquali, Antonella; Bazurro, Simone (Acta Biomedica Atenei Parmensis, 2025)
.